2021
DOI: 10.1039/d1nr04202e
|View full text |Cite
|
Sign up to set email alerts
|

Simple and high-yield preparation of carbon-black-supported ∼1 nm platinum nanoclusters and their oxygen reduction reactivity

Abstract: The improvement of oxygen reduction reaction (ORR) catalysts is essential before polymer electrolyte fuel cells can be used widely. To this end, we established a simple method for the size-selective...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…17(c)). 121 Among the Pt n /CB catalysts, Pt B51 /CB showed 2.1 times higher mass activity than the commercial Pt NPs/CB catalyst. On the basis of estimation of the electrochemical activity area and specific activity, we concluded that Pt n /CB shows higher ORR mass activity than commercial Pt NPs/CB because both the percentage of surface Pt atoms and specific activity of each surface Pt atom are higher for Pt n /CB than for commercial Pt NPs/CB.…”
Section: Activation Of Orr Electrode Catalystsmentioning
confidence: 93%
See 4 more Smart Citations
“…17(c)). 121 Among the Pt n /CB catalysts, Pt B51 /CB showed 2.1 times higher mass activity than the commercial Pt NPs/CB catalyst. On the basis of estimation of the electrochemical activity area and specific activity, we concluded that Pt n /CB shows higher ORR mass activity than commercial Pt NPs/CB because both the percentage of surface Pt atoms and specific activity of each surface Pt atom are higher for Pt n /CB than for commercial Pt NPs/CB.…”
Section: Activation Of Orr Electrode Catalystsmentioning
confidence: 93%
“…7(d)). 121 Unfortunately, the chemical compositions of these Pt n (PET) m (CO) l NCs cannot be controlled with atomic precision at present. Therefore, the chemical compositions and geometric structures of these NCs have not been accurately determined.…”
Section: Isolation Of Ag and Pt Ncsmentioning
confidence: 99%
See 3 more Smart Citations